Postoperative rehabilitation training adherence and influencing factors in adults with traumatic fractures in China: a cross-sectional study - Lu Tang; Shumei Shi; Ziyang Wang; Xiaochen Jiang; Renwei Zhang; Yangming Hu; Yihui Xing; Weifeng Wang; Xueling Qiu (BMJ Open)
Objective To explore rehabilitation training adherence as well as its related influencing factors among adult patients with traumatic limb fractures to provide a basis for clinical intervention strategies.Design Cross-sectional study.Setting Department of Rehabilitation Medicine.Participants Adults within 1 year postoperative for traumatic limb fractures and who underwent rehabilitation training were included in this study.Interventions Not applicable.Main outcome measures Patient information was collected using a self-designed general information form. Rehabilitation training adherence was evaluated using the Exercise Adherence Rating Scale (0/64, higher values=higher adherence). Barriers to and facilitators of rehabilitation were assessed using sociodemographic data, ability to perform daily life (ADL), General Self-Efficacy Scale (GSES) and Visual Analogue Scale. Pearson’s (r) and determination (R2) correlation coefficients were calculated to determine the strength of associations between variables. Potential correlates were explored using multiple linear regression analysis.Results Between December 2022 and December 2023, 170 subjects were recruited. The age of the participants ranged from 18 to 93 years, with a mean age of 41.5 years (SD 15.6). The mean Exercise Adherence score was 30.31 (SD 5.8). Adherence to postoperative rehabilitation training tended to be lower in participants of older age (−1.30; 95% CI −2.14 to −0.46; p=0.003), and those who had higher pain scores on the movement (moderate pain (−3.25; 95% CI −4.56 to −1.95; p<0.001) to severe pain (−5.42; 95% CI −7.31 to −3.54; p<0.001)), less education (−2.90; 95% CI −4.17 to −1.64; p<0.001), fewer family income (−1.82; 95% CI −2.77 to −0.87; p<0.001), treated at home (−1.90; 95% CI −3.35 to −0.45; p=0.011) and with lower GSES scores (0.25; 95% CI 0.16 to 0.34; p<0.001).Conclusions Patients with limb fractures require rehabilitation but often struggle with adherence to interventions. Strategies that focus on targeted education programmes, pain management and self-efficacy improvement may be considered to guide future research and programmatic approaches to enhance adherence to rehabilitation training.